Glycaemic and insulinemic response to dietary carbohydrates in horses. Issue 1 (October 2016) - Brøkner, Christine; Austbø, Dag; Næsset, Jon; Blache, Dominique; Knudsen, Knud; Hansen, Hanne; Tauson, Anne-Helene
Abstract Background Dietary sugar and starch affect plasma glucose and insulin concentrations. Little information is available about the effect of dietary fibre on plasma glucose and insulin concentration. It is hypothesized that different dietary fibre compositions will alter post-prandial glycaemic- and insulinemic index of test meals. The objective was to measure postprandial glucose and insulin concentrations in horses fed meals of different fibre compositions. Methods Blood was drawn via jugular vein puncture and the glycaemic and insulinemic index were calculated. Results The meal effect on glycaemic and insulinemic response followed the expected pattern, where plasma concentrations increased after feeding and declined after peak concentration. Glycaemic index was 100 (H), 102 (OB), 102 (BB) and 106 (M) and did not differ significantly between meals. Insulinemic index was 100 (H), 140 (OB), 121 (BB) and 125 (M) and did not differ significantly between meals. Conclusions In conclusion, meals containing different fibre compositions did not affect the glycaemic- and insulinemic index in horses.